The main influencing factors effecting the yield of maize - Sárvári, Mihály; Boros, Beáta (Acta Agraria Debreceniensis, 2010)
Maize is one of Hungary’s major cereals. In the 1970s and 1980s, we were in the frontline regarding yields and genetic advancement. However, yield fluctuation in maize has increased to 50-60% from 10-20% since the 1980s, which was partly caused by the increase in weather extremes due to climate change and by agrotechnical shortcomings.The experiments were carried out on typical meadow soil in four repetitions in the period of 2007-2008. In the sowing time experiment, sowing was performed on 10 April, 25 April, 15 May under a uniform fertilization of N120, P2O580 K2O 110 kg/ha. In the fertilization experiment, the yielding capacity of 10 hybrids with different genetic characteristics was studied in a control (non-fertilized) treatment and basic treatment of N40 P2O5 25, K2O 30 kg ha-1 active ingredient and a treatment with fivefold dosages of the basic treatment. In the plant density experiment, the relationship between plant density and yield was analysed at plant densities of 45, 60 and 75 thousand plants per ha. We found a tight correlation between sowing time and yield and grain moisture content at harvest. We found that grain moisture can be reduced by 5-10% by applying an earlier sowing time.The agroecological optimum fertilizer dosage was N 40-120, P2O5 25-75, K2O 30-90 kg ha-1 active ingredient at a plant density of 60-90 thousand plants ha-1 depending on the hybrid and the year.